Effects of Vacuum Drying on Structural Changes of Banana Slices - Wannapit Junlakan; Ram Yamsaengsung; Supawan Tirawanichakul (ASEAN Journal of Chemical Engineering, 2013)
The objective of this research was to study the optimum condition for the vacuum drying of banana slices using a vacuum dryer and to find out the appropriate thin layer equation for predicting the drying kinetic of bananas. The experiments were carried out at the drying temperatures of 60, 70, 80 and 90oC and absolute chamber pressure of 30 mmHg. The drying experiments were performed until the samples moisture content was lower than 3.4% (w.b.). Next, the dried products were analyzed for physical quality (in terms of color, shrinkage, and texture) and sensory quality (in terms of color, texture, flavor, crispness and overall acceptability). These data were used in choosing the optimum condition for the vacuum drying of banana slices. From experimental results, the drying time at the highest drying temperature was the shortest. At this condition, the dried banana slices showed the highest degree of yellowness, lower shrinkage, and more crispness compared to lower drying temperatures. From sensory analysis, each drying condition showed significant effect on consumer acceptability with the drying temperature of 70, 80 and 90oC showing the levels of the overall acceptability sensory qualities of dried banana is not significantly different. Consequently, the drying temperature of 90oC was suggested as the best drying condition for sliced bananas. Moreover, three mathematical models (Newton, Logarithmic and Page) describing thin layer drying were investigated. It was found that the thin layer equation providing the highest coefficient of determination (R2) and the lowest chi-square (X2) and root mean square error (RMSE) was the Logarithmic equation.